Trafficking, lateral mobility and segregation of the plant K+ channel KAT1 - Reuff, Muriel; Mikosch-Wersching, Melanie; Homann, Ulrike (Plant biology, 2010)
Functioning of ion channels depends not only on the control of their activity but also on their density and lateral organisation in the membrane. The two latter aspects have recently attracted increasing attention. Here, we summarize studies on trafficking and plasma membrane distribution of the plant K+ channel KAT1 from Arabidopsis thaliana. In guard cells, KAT1 was found to be subject to constitutive and pressure-driven turnover and ABA-stimulated endocytosis. These results point to a role of exo- and endocytosis in regulating KAT1 density and thus ion transport during guard cell functioning. Recent studies indicate that KAT1 density can also be adjusted at the site of ER export. Efficient ER export of KAT1 was shown to depend on an acidic motif that interacts with Sec24, a component of ER-derived vesicles. Surface expression of ER export mutants of KAT1 can be rescued through heterotetrameric assembly with wild-type KAT1, implying that not all subunits of the channel tetramer need to carry an ER export motif. Analysis of the distribution of KAT1 in the plasma membrane revealed segregation of the channel into microdomains, and low lateral mobility in both plant and mammalian cells. In plant cells, SNAREs have been shown to be involved in anchoring KAT1 in the plasma membrane. Studies on guard cells imply a role for the cell wall in organisation of KAT1 microdomains. Together, these findings underline the importance of investigating mechanisms of KAT1 trafficking and lateral organisation in order to fully understand channel functioning.